Weili Wangque de Jinian - Wei, Liu (China, 2009)
The film is the memory of the filmmaker's sophomore year of 1989 in China, when he was almost killed. Twenty years have passed and silence, oblivion and denial have erased the memory of those events and made everything that happened obscure and distorted.
Verzio Film Festival Submission
Keywords: Documentary films